Effect of Serum Copper on Circulating Angiogenesis-related Factors in Women withPreeclampsia - Najm Nadheer, Khalid; Abdul Aziz abdul Hussein, Afaq; Kadhem Al-Hakeim, Hussein (International Journal of Psychosocial Rehabilitation, 2022)
Preeclampsia (PE) is characterized by a series of clinical features such as hypertension and proteinuria associated with endothelial dysfunction and the impairment of placenta vascular endothelial integrity. This study aimed to investigate the effect of serum copper (Cu) level on some angiogenesis-related factors including vascular endothelial growth factor-A (VEGF-A), soluble Fms-like tyrosine kinase-1 (sVEGF-R1), soluble endoglin (sEng) and ceruloplasmin (CP) in Iraqi women with PE and control pregnant women. Therefore, 60 women with PE in addition to 30 healthy pregnant women were enrolled in the study. Serum concentration of sEng, VEGF-A, sVEGF-R1, and Cu in PE group significantly increased (p<0.05) in the PE group compared with that in the control group. Increased production of antiangiogenic factors, soluble VEGF-A and sEng contribute to the pathophysiology of PE, indicating the involvement of these parameters in the angiogenic balance in patients with PE. Tests for between-subject effects showed that the circulating angiogenesis factors and Cu were significantly associated with the presence of PE. Serum Cu level was significantly correlated with VEGF- A and VEGF-R1 levels but not with sEng. Multiple regression analysis revealed that only Cp and BP can significantly predict the complications in women with PE. In conclusion, serum Cu has a role in the angiogenesis in women with PE and may be a new drug target in the prevention or treatment of PE.